THE IMPORTANCE OF SOCIAL RELATIONS IN THE FORMATION OF THE SOCIAL CONSCIOUSNESS OF PRESCHOOL CHILDREN - Ganiyeva Dildora Muqimovna,; Xamidova Xumora, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the identification and justification of the interaction of the concept of moral behavior in preschool children with psychological and social moral characteristics in children.